A Systematic Review of Single-Case Research Studies on Using Video Modeling Interventions to Improve Social Communication Skills for Individuals With Autism Spectrum Disorder. (December 2018) - Qi, Cathy Huaqing; Barton, Erin E.; Collier, Margo; Lin, Yi-Ling
Video modeling (VM) interventions have increasingly been examined as a means of teaching social communication skills to individuals with autism spectrum disorder (ASD). However, the research, which primarily used single-case research designs (SCRDs), pointed to inconsistent results across participants within studies and across studies. The purpose of this review was to synthesize 24 research studies using SCRD to examine the effects of VM for individuals with ASD on social communication skills. We applied the What Works Clearinghouse (WWC) SCRD design standards, conducted our own independent visual analysis, and calculated four nonoverlap indices to synthesize this research. Findings from the synthesis of the 24 SCRD studies concluded that VM intervention is an evidence-based practice according to the WWC standards for increasing social communication skills of individuals with ASD. Implications for future research and practice are discussed.